2016
DOI: 10.1038/srep38075
|View full text |Cite
|
Sign up to set email alerts
|

J-curve relation between daytime nap duration and type 2 diabetes or metabolic syndrome: A dose-response meta-analysis

Abstract: Adequate sleep is important for good health, but it is not always easy to achieve because of social factors. Daytime napping is widely prevalent around the world. We performed a meta-analysis to investigate the association between napping (or excessive daytime sleepiness: EDS) and the risk of type 2 diabetes or metabolic syndrome, and to quantify the potential dose-response relation using cubic spline models. Electronic databases were searched for articles published up to 2016, with 288,883 Asian and Western s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 55 publications
5
44
1
1
Order By: Relevance
“…Interestingly, this finding is in line with previous studies reporting a J curved relationship between nap duration and CVD 11 and cardiovascular risk factors, such as diabetes and metabolic syndrome. 12 However, the increased risk of CVD events for frequent nappers disappeared in adjusted analyses. Regarding the underlying causes of our findings, we could speculate that frequent napping may be secondary to impaired sleep quality due to a chronic condition, which may represent an independent risk factor for CVD events.…”
Section: Nap Frequency and Incidence Of Cvd Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, this finding is in line with previous studies reporting a J curved relationship between nap duration and CVD 11 and cardiovascular risk factors, such as diabetes and metabolic syndrome. 12 However, the increased risk of CVD events for frequent nappers disappeared in adjusted analyses. Regarding the underlying causes of our findings, we could speculate that frequent napping may be secondary to impaired sleep quality due to a chronic condition, which may represent an independent risk factor for CVD events.…”
Section: Nap Frequency and Incidence Of Cvd Eventsmentioning
confidence: 99%
“…11 Interestingly, a J curved relationship was also reported between nap duration and diabetes and metabolic syndrome. 12 A large study (n=116 632) reported that, compared with nonnappers, the risk of CVD increased for subjects napping ≤1 hour and was highest for subjects napping >1 hour. 13 In contrast, in the Greek cohort study, a lower risk for coronary mortality was found for subjects taking naps of any duration.…”
Section: And Amentioning
confidence: 99%
“…Daytime napping has been associated with increased risk for impaired glucose metabolism and diabetes 36 , microvascular disease 81 , and metabolic syndrome 37 in adults. Yamada and colleagues further examined the dose-response relationship and reported that napping up to about 40 minutes/day showed no association with the risk of developing type 2 diabetes or metabolic syndrome versus no nap, followed by a sharp increase in risk at longer nap times 37 . Such adverse effect was not present in the whole sample, but it was evident in the 5th graders of our study.…”
Section: Napping Effects On Metabolic Healthmentioning
confidence: 99%
“…A recent systematic review by Thorpe et al summarized the developmental impact of naps during the first 5 years of life and reported mixed findings on behavioral, emotional, and healthrelated outcomes 35 . The effect of napping on glucose metabolism and diabetes in adults is controversial, with some studies reporting a negative effect of napping on glucose metabolism and diabetes and others failing to find a significant effect 36,37 . Such inconsistencies may be due to uncontrolled confounding from sociodemographics, comorbidity, night-time sleep, and Downloaded from https://academic.oup.com/sleep/advance-article-abstract/doi/10.1093/sleep/zsz126/5499200 by University of California, Irvine user on 05 July 2019 A c c e p t e d M a n u s c r i p t 5 inadequate measure of napping frequency and duration [38][39][40][41] .…”
Section: Introductionmentioning
confidence: 99%
“…Ученые из Токийского университета провели метаанализ работ, в которых изучалась связь между дневным сном и диабетом, в общей сложности охвативших более 300 000 людей азиатского и европейского происхождения, проживающих в разных уголках мира. В результате обнаружилось, что при продолжительности дневного сна более 40 мин значительно увеличивается риск развития сахарного диабета 2-го типа [10].…”
Section: сон и сахарный диабетunclassified